(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Procalcitonin is a sensitive biomarker for bacterial infections. Recent studies show a correlation between serum procalcitonin level and vesicoureteral reflux (VUR). The aim of this study was to evaluate the predictive value of procalcitonin in diagnosis of VUR in children with febrile urinary tract infection. Material and Methods. One hundred and eight children aged 2 month to 12 years with febrile urinary tract infection were evaluated. Serum procalcitonin was measured before initiation of antibiotics. Standard voiding cystourethrography (VCUG) was performed in all children as the gold standard for detection of VUR. Sensitivity and specificity of a high procalcitonin level was evaluated using the receiver operating characteristic curve. Results. Forty-eight patients (44%) had VUR at least in one kidney, including grade 1 to 2 in 12 patients (11.1%), grade 3 in 16 (14.8%), and grade 4 to 5 in 20 patients (18.5%). Procalcitonin level ranged from 0.05 ng/mL to 13.6 ng/mL. Procalcitonin level was significantly higher with increasing the grading of reflux. Comparing procalcitonin levels with VCUG results, a sensitivity of 97% and a specificity of 75% was obtained at a procalcitonin level of 0.59 ng/mL for diagnosis of VUR. There was a significant correlation between procalcitonin level and leukocytosis, erythrocyte sedimentation rate, and C-reactive protein. Conclusions. A high procalcitonin level may be used for prediction of all grades of VUR in children with febrile urinary tract infection. A low procalcitonin level may be used for avoidance of unnecessary VCUG in some low-risk patients.